Photoionization study of Ne-like K9+, Ca10+, Sc11+, Ti12+, V13+, Cr14+, Mn15+, and Fe16+ ions using the screening constant by unit nuclear charge method. (August 2016) - Goyal, Arun; Khatri, Indu; Sow, Malick; Sakho, Ibrahima; Aggarwal, Sunny; Singh, A.K.; Mohan, Man
Abstract: Photoionization of the 2s 2 2p 6 ( 1 S0 ) ground state of the Ne-like ( Z =19–29) ions is presented in this paper. Resonance energies and total natural width of the 2s2p 6 n p 1 P series of the Ne-like K 9+, Ca 10+, Sc 11+, Ti 12+, V 13+, Cr 14+, Mn 15+, and Fe 16+ are reported. All the calculations are made using the Screening constant by unit nuclear charge (SCUNC) formalism. New data for Ne-like K 9+, Sc 11+, Ti 12+, V 13+, Cr 14+, and Mn 15+ ions are tabulated. Good agreements are found with available literature data. Highlights: Photoionization of ground state of the Ne-like ( Z =19–29) presented. good agreements with scarce literature data. New data for Ne-like K 9+, Sc 11+, Ti 12+, V 13+, Cr 14+, and Mn 15+ ions. Useful guidelines for application in laboratory, astrophysics, and plasma physics.